Psychological Support for Health Professionals: An Interpretative Phenomenological Analysis - Volpato, Eleonora; Banfi, Paolo Innocente; Valota, Chiara; Pagnini, Francesco (Frontiers in Psychology, 2018)
Background: The work of health care professionals (HCPs) exposes them to emotionally difficult situations, anxiety, suffering and death, so they are at risk of burnout. Objectives: To describe HCPs’ experiences of a psychological support intervention and its influence on the daily work of a sample caring for patients with neuromuscular and chronic respiratory illnesses. Methods: This exploratory, descriptive, qualitative study was carried out at the Respiratory Rehabilitation Unit of IRCCS Santa Maria Nascente, in Milan, Italy. Semi-structured interviews with a purposive sample of 10 HCPs were subjected to interpretative phenomenological analysis (IPA). Results: Five related themes emerged: psychological support; repeating the experience; relationships; the role of homework; competences. HCPs perceived that the intervention influenced their daily life, giving them a secure base and a new perspective on their professional role. Conclusions: Psychological support interventions may not be appropriate for all HCPs, but they may help some HCPs to handle the demands of a stressful work life. Further studies are needed to determine its efficacy in reducing stress and prevent burnout.